Women's Socio-Cultural Status in the Tharu Community: A Case of Janaki Rural Municipality, Kailali - Adhikari, Kanshi Prasad (Academia Research Journal, 2024)
Nepal, characterized by its multi-ethnic composition, hosts a diverse population of approximately 125 castes and ethnic groups, each with distinct cultural practices and beliefs. Among these groups, the Tharu people constitute a significant indigenous community, comprising about 6.6% of Nepal's total population. Historically settled in the Terai region, near forested areas and the Inner Terai, Tharus are culturally and linguistically diverse, with distinct sub-groups dispersed across various regions of Nepal.Tharu society traditionally embodies a rich cultural heritage, marked by unique customs and attire. Despite their agricultural prowess and reliance on forest resources for livelihoods, Tharu women face significant socio-economic challenges. They are often relegated to domestic and subsistence roles, with limited access to education and economic resources compared to men. While some sub-groups within the Tharu community exhibit exceptions to these norms, such as the Rana Tharus with their female-dominant societal structure, broader societal and economic barriers persist. This study focuses on Janaki Rural Municipality of Kailali district, aiming to explore the socio-cultural status of Tharu women. Through structured questionnaires, interviews, and observations, the research investigates household decision-making dynamics, educational disparities, and barriers hindering women from achieving higher social standing. The findings underscore the complex interplay of cultural norms, gender roles, and socio-economic factors influencing the status of Tharu women within their community. This research contributes to a deeper understanding of gender dynamics and social inequalities among Nepal's Tharu population, offering insights for targeted interventions to improve their socio-cultural and economic conditions.